Revised map of European aeolian deposits derived from soil texture data. (15th August 2021) - Bertran, Pascal; Bosq, Mathieu; Borderie, Quentin; Coussot, Céline; Coutard, Sylvie; Deschodt, Laurent; Franc, Odile; Gardère, Philippe; Liard, Morgane; Wuscher, Patrice
Abstract: European aeolian deposits have been mapped using the LUCAS topsoil texture database and the location, thickness and grain size mode of loess sections described in the literature have been compiled. The map, in fairly good agreement with those based on a classical geological approach, has the advantage of being of equal precision for the whole study area and makes it possible to highlight grain size gradients. It shows three main types of aeolian systems, i.e. systems associated with ice sheets (FIS, BIIS, AIS) and the rivers they feed, continental systems related to the erosion of sedimentary rocks, and coastal systems. Each aeolian system is comprised of a band of coversands of varying extent close to the sources and bands of sandy loess and loess away from the sources. The thickness of loess is highly variable throughout Europe. The areas of greatest accumulation are associated with the rivers draining the AIS (Rhine, Danube, Rhône). The Middle Danube, which combines sources of glacial origin (AIS) and local sources, constitutes the main accumulation area in Europe. Conversely, continental and coastal systems generated only limited loess cover. The latitudinal gradient of vegetation probably played an important role in loess sedimentation during the LGM. Weak interference between particle transport and vegetation (periglacial desert in the sand belt, cryptogamic crusts and steppe in the north European loess belt) allowed for particle sorting through aeolian transport to develop. The loess band is extensive in low-relief areas and is typified by a low sand content. In southern Europe, on the other hand, the capture of saltating and suspended particles by the shrubby steppe vegetation led to the dominant accumulation of sandy loess near sources. Highlights: Cartography of European aeolian deposits based on LUCAS topsoil texture database. Main types of aeolian systems: glacial, coastal, continental and mixed. Main loess accumulations along rivers draining the AIS and mixed systems. Latitudinal gradient in sandy loess belt development due to vegetation.